Treatment of delocalized electron transfer in periodic and embedded cluster DFT calculations: The case of Cu on ZnO (10 1¯0). Issue 32 (3rd November 2015) - Hellström, Matti; Spångberg, Daniel; Hermansson, Kersti
Abstract : We assess the consequences of the interface model—embedded‐cluster or periodic‐slab model—on the ability of DFT calculations to describe charge transfer (CT) in a particularly challenging case where periodic‐slab calculations indicate a delocalized charge‐transfer state. Our example is Cu atom adsorption on ZnO(10 1 ¯ 0), and in fact the periodic slab calculations indicate three types of CT depending on the adsorption site: full CT, partial CT, and no CT. Interestingly, when full CT occurs in the periodic calculations, the calculated Cu atom adsorption energy depends on the underlying ZnO substrate supercell size, since when the electron enters the ZnO it delocalizes over as many atoms as possible. In the embedded‐cluster calculations, the electron transferred to the ZnO delocalizes over the entire cluster region, and as a result the calculated Cu atom adsorption energy does not agree with the value obtained using a large periodic supercell, but instead to the adsorption energy obtained for a periodic supercell of roughly the same size as the embedded cluster. Different density functionals (of GGA and hybrid types) and basis sets (local atom‐centered and plane‐waves) were assessed, and we show that embedded clusters can be used to model Cu adsorption on ZnO(10 1 ¯ 0), as long as care is taken to account for the effects of CT. © 2015 Wiley Periodicals, Inc. Abstract : Cu/ZnO catalysts, used in industry for the production of methanol, are difficult to model using computational chemistry methods. This article compares how well two very different structural models (periodic slabs and embedded clusters) describe the binding between Cu and ZnO in a model system where electrons sometimes are transferred between the two components.